2016
DOI: 10.1021/acssuschemeng.6b00716
|View full text |Cite
|
Sign up to set email alerts
|

Striving Toward Visible Light Photocatalytic Water Splitting Based on Natural Silicate Clay Mineral: The Interface Modification of Attapulgite at the Atomic-Molecular Level

Abstract: Development of visible light driven photocatalytic water splitting catalysts for hydrogen production with both high activity and stability has remained a challenge to renewable energy research in the past decades. Herein, for the first time, the interface modified attapulgite (ATP) at the atomic-molecular level was employed as a photocatalyst for hydrogen production from water under visible light illumination. Because of the enhancement of the surface hydroxyl, the increase of dye adsorption, and high efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Probably because of this reason, the enhanced photocatalytic abilities of clay-based photocatalysts are generally attributed to high adsorption properties and excellent surface properties for improving the dispersity and specific surface area of semiconductors . Some works reported that the clay can be used as charge transfers, but these clays usually need to introduce an additional photosensitizer. , Interestingly, the iron-rich clay itself such as kaolinite and montmorillonite revealed some photocatalytic activities because of existence of photoactive iron oxides which are mainly structural iron in the aluminosilicate lattice, resulting from isomorphous substitution. These clays improved the photogenerated carrier transfer efficiency of the supported photocatalyst because of its semiconducting property . Although a few works have reported a semiconductor–clay based photocatalyst, the essential roles of the iron-rich clay on the separation of photogenerated carriers remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Probably because of this reason, the enhanced photocatalytic abilities of clay-based photocatalysts are generally attributed to high adsorption properties and excellent surface properties for improving the dispersity and specific surface area of semiconductors . Some works reported that the clay can be used as charge transfers, but these clays usually need to introduce an additional photosensitizer. , Interestingly, the iron-rich clay itself such as kaolinite and montmorillonite revealed some photocatalytic activities because of existence of photoactive iron oxides which are mainly structural iron in the aluminosilicate lattice, resulting from isomorphous substitution. These clays improved the photogenerated carrier transfer efficiency of the supported photocatalyst because of its semiconducting property . Although a few works have reported a semiconductor–clay based photocatalyst, the essential roles of the iron-rich clay on the separation of photogenerated carriers remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving the goals of high H 2 production rate and low electricity costs, the most critical research needs are to develop novel and cost-effective electrocatalysts to replace platinum (Pt) catalysts. Therefore, it is highly attractive to explore cost-effective electrocatalysts deriving from earth-abundant metal compounds. Recently, the two-dimensional transition metal chalcogenides, for example, MoS 2 , MoSe 2 , CoS 2 , WS 2 , and WSe 2 , have been extensively investigated. , Among them, MoS 2 nanoparticles showing excellent electrocatalytic HER performance have received great interest in recent studies. High electrocatalytic activity of amorphous molybdenum sulfide has been reported in a series of recent studies. , The high activity of amorphous MoS 2 is attributed by the coordinatively unsaturated sulfur atoms. , Furthermore, the amorphous MoS 2 is comprised of unsaturated and/or terminal S 2 2– ligands as well as apical and/or bridging S 2 2– ligands sites, which is analogous to the thiomolybdate [Mo 3 S 13 ] 2– clusters. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Now we have to face the increasingly serious water pollution problems with the rapid development of global industrialization . Especially, dyeing wastewater generated from the textile industry is one of the industrial pollutant headstreams.…”
Section: Introductionmentioning
confidence: 99%